Volcanic hazard at hydraulically-charged ocean island volcanoes : the case of Flores Island (Azores) - Andrade, Mariana (2023)
The interaction of ascending magmas with groundwater at near-surface levels may produce violent explosive eruptions, turning relatively mild basaltic volcanism into a highly hazardous force. Yet this effect is often underrated or overlooked, particularly at hydraulically-charged ocean island volcanoes. This PhD project studied the recent (Holocene) volcanic record of Flores Island (Azores Archipelago) in order to understand how the hazard potential of small-volume monogenetic eruptions at hydraulically-charged island edifices is enhanced by water/magma interactions, and how volcanic hazard may be modified by rainfall variability at decadal, centennial, or millennial time scales. Using lake and subaerial tephrostratigraphy, geochronology, geomorphology and glass shard geochemistry, this study shows that Flores experienced at least six eruptions during the Holocene, taking place at 6280, 4490, 3430, 3330, 3250, and 3180 cal yr BP, mostly sourced from two centres of volcanic activity: Funda (FVS) and Comprida (CVS) Volcanic Systems. These eruptions assumed a variety of eruptive styles, including Hawaiian-Strombolian, violent Strombolian, and phreatomagmatic (Taalian style), often with more than one style during the same eruption. Critically, eruption reconstructions show that groundwater played an important role in the FVS and CVS, by transforming low-explosivity basaltic eruptions into highly explosive phreatomagmatic events. Water/magma interactions at Flores are apparently controlled by variations in eruption rates, associated with erosion and widening of volcanic conduits, with long-term rainfall variability having a limited correlation with phreatomagmatism, given that even in periods with negative anomalies of precipitation, groundwater is ubiquitously available. This study thus reinforces the notion that, on island volcanoes saturated with near-surface aquifers and subjected to small-volume monogenetic volcanism, eruption rates have a determining role in triggering phreatomagmatism and consequently amplifying volcanic hazard. Finally, this study also brings to the fore the need for more comprehensive assessments of volcanic hazard for settings similar to Flores Island.